2018
DOI: 10.1038/s41598-018-30404-x
|View full text |Cite
|
Sign up to set email alerts
|

Topical administration of EGF suppresses immune response and protects skin barrier in DNCB-induced atopic dermatitis in NC/Nga mice

Abstract: Atopic dermatitis (AD) is a common inflammatory skin disease characterized by a complex, heterogeneous pathogenesis including skin barrier dysfunction, immunology, and pruritus. Although epidermal growth factor (EGF) is essential for epithelial homeostasis and wound healing, the effect of EGF on AD remains to be explored. To develop a new therapy for AD, the anti-AD potential of EGF was investigated by inducing AD-like skin lesions in NC/Nga mice using 2,4-dinitrochlorobenzene (DNCB). EGF was administrated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 61 publications
4
72
0
Order By: Relevance
“…Recently, it has been shown that topical administration of EGF suppresses immune response and protects skin barrier in DNCB‐induced ADin NC/Nga mice. This effect appeared to be the result of EGF upregulation of epidermal proteins and downregulation of TSLP (thymic stromal lymphopoietin)‐mediated mast cell and Th2 cell activation . Therefore, we propose that in subsets of patients with EGF deficiency, replacement therapy with topical or systemically administered EGF may be of clinical value.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, it has been shown that topical administration of EGF suppresses immune response and protects skin barrier in DNCB‐induced ADin NC/Nga mice. This effect appeared to be the result of EGF upregulation of epidermal proteins and downregulation of TSLP (thymic stromal lymphopoietin)‐mediated mast cell and Th2 cell activation . Therefore, we propose that in subsets of patients with EGF deficiency, replacement therapy with topical or systemically administered EGF may be of clinical value.…”
Section: Discussionmentioning
confidence: 94%
“…These findings supported that sustaining a close to normal kidney function is an integral component of the tolerized phenotype. Several genes involved in immune regulation, such as Egf ( 34 ) and S100g ( 35 ), also showed significantly heightened expression in kidney cells from tolerized and naive kidneys in comparison with those from rejecting kidneys ( Supplemental Figure 2B ). In contrast, the expression of chemokine genes such as Ccl5 and Ccl8 was significantly enhanced in kidney cells from rejecting kidneys in comparison with those from tolerized or naive kidneys ( Supplemental Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Immunoreactivities of TNF-α, interleukins and HMGB1 were analyzed from the 7 sections per mouse according to a published protocol [ 26 ] with modification. Their images were taken in the tissue area of 70 μm 2 of the dorsal skin using an AxioM1 light microscope (Carl Zeiss, Oberkochen, Germany) equipped with a digital camera (DP72) (Olympus, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…To examine the expression levels of TNF-α, IL-1β, IL-4 and IL-13, western blot analyses were carried out in accordance to our previous study with modification [26]. Briefly, seven animals per group were sacrificed under deep anesthesia by intraperitoneal injection of pentobarbital sodium (60 mg/kg) (JW Pharm.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation